(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Astute agriculture has been altered by the Internet of Things (IoT), which has increased efficiency and reduced production costs while improving productivity and optimizing resource utilization. This article discusses the future of automation and the use of sensors and IoT in greenhouse farming. Various factors such as humidity, the potential of hydrogen (pH) and electrochemical value, temperature, ultraviolet (UV) light intensity, and carbon dioxide (CO2) level are recorded using a range of sensors to offer important insight into early defect identification and diagnosis. Fog computing is an emerging computing technology for enhancing and supporting cloud computing. Fog computing platforms include a variety of properties that allow them to offer services to users more rapidly and enhance the Quality of Service (QoS) of IoT devices, such as proximity to edge users, openness, and mobility support. Consequently, it's becoming an important approach for user-centered IoT-based apps. A Decision Support System (DSS) in the Fog layer described in this article is the entire operating system that supervises and oversees all activities. We offer an energy-aware allocation technique for deploying application modules (tasks) on Fog devices and an appropriate Green home management system based on Machine learning. The suggested method's simulation is assessed using several performance measures. The results reveal that the suggested machine learning approach in the Fog IoT environment is more efficient than the other energy conservation and greenhouse gas management methods.